Understanding A.M. Iqbal’s Vision on Perfect Man - Imam Bahroni (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2013)
This article tries to elucidate A.M Iqbal’s vision on the concept of perfectman. Its significance is at the point that Man can transform both his being andhis surroundings according to his own desires and aspirations. He actually makesimprovements upon what is created by God. God created night, he inventedthe lamp; God created clay, and from it he made the cup; God created deserts,mountains, forests, orchards, gardens, and groves. He makes glass out of stoneand turns poison into an antidote. God created the world, but he made it morebeautiful.Iqbal’s reasoning amply justifies belief in the ascendancy of man overthe universe and his predicted perfection. The perfect man is the ultimate endof the revolutionary process, and he is developed out of the present man, justas the full moon is developed from the crescent.